Daya Serap Mangrove Rhizophora sp. Terhadap Logam Berat Timbal (Pb) Di Perairan Mangrove Park, Pekalongan - Endang Supriyantini; Ria Azizah Tri Nuraini; Cintya Pramesthi Dewi (Jurnal Kelautan Tropis, 2017)
Human activities in the Mangrove Park waters, Pekalongan area can  be increasing the present of heavy metal in acuatiq environmental and aquatic organisms. The purpose of this research is (1) to know the heavy metal content of Pb in water, sediment, root and mangrove leaves Rhizophora sp; (2) to know the level of Pb heavy metal pollution in Mangrove Park area; (3) Bioconcentration factor (BCF) on root and Rhizophora sp.This research was conducted in November 2015 and January 2016. The materials used in this study are water samples, sediments, roots, and leaves Rhizophora sp. The method of determining the location of research stations based on Purposive Sampling Method. Analyze heavy metal Pb using AAS (Atomic Absorption Spectrophotometry) at the Laboratory of Center for Industrial Pollution Prevention Technology (BBTPPI). The results showed that in Mangrove Park waters, Pekalongan has not polluted Pb metal since it has not exceeded the determined threshold limit. The content of Pb in sediment is still below the specified quality standard of 12.06-14.77 mg / kg (November 2015) and 10.65-13.26 mg / kg (January 2016). The content of Pb at the root is 0.25-0.32 mg / kg (November 2015) and 0.15-0.47 mg / kg (January 2016). The content of Pb metal on leaves is 0.17-0.22 mg / kg (November 2015) and 0.17-0.59 mg / kg (January 2016). Based on the bioconcentration factor, the ability of Rhizophora sp. In accumulating Pb metals is low.  Kegiatan manusia di kawasan Perairan Mangrove Park, Pekalongan dapat meningkatkan kehadiran logam berat di lingkungan perairan dan organisme air. Tujuan penelitian ini adalah (1) untuk mengetahui kandungan logam berat Pb dalam air, sedimen, akar dan daun mangrove Rhizophora sp. di kawasan Mangrove Park Pekalongan;(2) mengetahui tingkat pencemaran logam berat Pb di kawasan Mangrove Park Pekalongan; (3) Mengetahui Biokonsentrasi Faktor (BCF) pada akar dan daun Rhizophora sp. Penelitian dilakukan pada bulan November 2015 dan Januari 2016. Materi yang digunakan untuk penelitian adalah sampel air, sedimen, akar, dan daun Rhizophora sp. Metode penentuan lokasi penelitian berdasarkan Purposive Sampling Method. Analisis logam berat Pb menggunakan AAS (Atomic Absorption Spectrophotometry) di Laboratorium Balai Besar Teknologi Pencegahan Pencemaran Industri (BBTPPI). Hasil penelitian menunjukkan di perairan Mangrove Park, Pekalongan belum tercemar logam Pb karena belum melebihi batas ambang yang ditentukan. Kandungan Pb dalam sedimen masih dibawah baku mutu yang ditentukan yaitu 12.06-14.77 mg/kg (November 2015) dan 10.65-13.26 mg/kg (Januari 2016). Kandungan Pb pada akar sebesar 0.25-0.32 mg/kg (November 2015) dan 0.15-0.47 mg/kg (Januari 2016). Kandungan logam Pb pada daun 0.17-0.22 mg/kg (November 2015) dan 0.17-0.59 mg/kg (Januari 2016). Berdasarkan factor biokonsentrasi, kemampuan Rhizophora sp. dalam mengakumulasi logam Pb tergolong rendah.